Body Upload 2.0: Downloadable Cosmetic [Re]Birth. - NGUYEN, Kathy (Ekphrasis (2067-631X), 2017)
Hans Moravec's Robot: Mere Machine to Transcendent Mind remarkably blueprints a future where rapid technological feats will grant humans the ability to upload/ download their consciousness into computer software and/ or computer chips, preserving their lifelong memories and identities. This blueprint is edified by Robert Mitchell's and Phillip Thurtle's book, Data Made Flesh: Embodying Information, further problematizing the im/material and immortalized information/terminal fleshy bodies. These dichotomies are shattered as bodies and information become innate scions, continually grafting onto the other's multilayered epidermis. Flesh is transfigured into information and information is transfigured into flesh. Bodies are edified by information; corporeality and dis/embodiment are further problematized while we live in the age of informatics. Interesting questions arise as a result: What does it mean to have -or occupy - a body when it becomes part of a downloadable network? Advantageous, directed by Jennifer Phang, depicts a future where female bodies are continually represented as easily replaceable vessels. It is my contention that Advantageous cinematically presents a future where digitized mechanical reproduction is possible. Bodies become updated, evolving into informatically-structured bodies. Following a similar cinematic line of vision, Oshii Mamoru's film Ghost in the Shell 2: Innocence depicts how human consciousness is artificially implanted onto sex dolls, reproducing them into sentient gynoids. Thus, the innate grafting between flesh and data becomes more prominent in these films: consciousness is downloadable, while the body updates itself. In this paper, I argue that the experimental bodies depicted in Advantageous and to a lesser extent, Innocence, illustrate how downloading - or uploading -the consciousness/information from the organic brain to a new shell, a younger body, represents a form of mechanical reproduction. These films theoretically visualize how downloading the body signifies that while bodies are terminal, the mind -microchipped -is not. Life and death become more optically blurry.